2012
DOI: 10.1371/journal.pone.0044723
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Use of Personal Protective Equipment among Chinese Critical Care Clinicians during 2009 H1N1 Influenza Pandemic

Abstract: BackgroundCritically ill patients with 2009 H1N1 influenza are often treated in intensive care units (ICUs), representing significant risk of nosocomial transmission to critical care clinicians and other patients. Despite a large body of literature and guidelines recommending infection control practices, numerous barriers have been identified in ICUs, leading to poor compliance to the use of personal protective equipment (PPE). The use of PPE among critical care clinicians has not been extensively evaluated, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 31 publications
(58 reference statements)
3
67
2
4
Order By: Relevance
“…Nevertheless, the 2009 H1N1 influenza pandemic taught us that knowledge and self-reported compliance to recommended PPE use are suboptimal among HCWs. 8 More than 850 confirmed HCW infections were reported from Guinea, Liberia, and Sierra-Leone in the recent EVD outbreak with more than 500 reported deaths (see http://www.cdc.gov/vhf/ebola/ outbreaks/2014-west-africa/index.html). Three cases of nosocomial transmission among apparently protected HCWs in Spain and the United States heightened concerns among health care professionals and decision makers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the 2009 H1N1 influenza pandemic taught us that knowledge and self-reported compliance to recommended PPE use are suboptimal among HCWs. 8 More than 850 confirmed HCW infections were reported from Guinea, Liberia, and Sierra-Leone in the recent EVD outbreak with more than 500 reported deaths (see http://www.cdc.gov/vhf/ebola/ outbreaks/2014-west-africa/index.html). Three cases of nosocomial transmission among apparently protected HCWs in Spain and the United States heightened concerns among health care professionals and decision makers.…”
mentioning
confidence: 99%
“…13,14 Nevertheless, most studies were conducted in a hospital setting and were based on self-reported questionnaires without matched objective observations. 8 Moreover, studies were not conducted in settings of a severe contagious outbreak in which participants need to combine contact, droplet, and airborne precautions.…”
mentioning
confidence: 99%
“…3 More recently, a study of 21 intensive care units in China found that 55% of health care workers complied with the proper use of FPE. 4 Two studies from Canada found 44% of nurses in 6 hospitals 5 and 11% of doctors in 14 hospitals reported they properly adhered to FPE. 6 Such suboptimal adherence rates are of great concern because it is estimated that 1 in 4 health care workers contract a communicable respiratory illness through work.…”
mentioning
confidence: 99%
“…Esse resultado também foi encontrado em uma pesquisa realizada em 50 municí-pios de Minas Gerais 29 . Assim como na literatura pesquisada 17,[20][21][22][23][24] houve maior frequência de acidentes por exposição percutânea, provavelmente pelo fato de a dimensão da superfície corporal cutânea ser maior que a mucosa e estar diretamente envolvida no manuseio de instrumentos durante a realização dos procedimentos 23 . O sangue foi o material biológico de maior predominância nos acidentes em estudo, causados principalmente pelo uso de agulhas, instrumento que mais contribuiu para os acidentes com exposição percutânea.…”
Section: Métodosunclassified